Low-level laser therapy on soft tissue healing after implantation: a randomized controlled trial - Qiaoru Zou; Shengxiang Zhang; Chunwen Jiang; Shan Xiao; Yue Wang; Bing Wen (BMC Oral Health)
Abstract Background To explore the effect of low-level laser therapy (LLLT) on the healing of soft tissue around the implant after flap implantation and explore the possible mechanism. Methods A total of 58 patients who underwent implant surgery were enrolled, with a total of 70 implants. They were randomly divided into the LLLT group and the control group. The LLLT group underwent LLLT with Nd:YAG (Fotona, 1064 nm) immediately after surgery and on the 2nd and 3rd day in the surgical area, while the control group did not receive any intervention. Pain assessment was performed in the first 3 days after surgery. The weight of peri-implant crevicular fluid (PICF), modified sulcus bleeding index (mSBI), gingival index (GI), and the expression levels of tumor necrosis factor-α (TNF-α), and vascular endothelial growth factor (VEGF) on the 7th and 14th days after surgery were evaluated. Results On the first 3 days after surgery, the pain score of the LLLT group was significantly lower than that of the control group. On the 7th and 14th day after surgery, the PICF volume, mSBI, GI, and TNF-α levels of the LLLT group were lower than those of the control group. The VEGF levels in the LLLT group were significantly higher than that in the control group. Conclusions LLLT can promote the healing of the soft tissue after implantation, effectively relieve postoperative pain, improve clinical indicators, reduce TNF-α, and increase the expression level of VEGF, which is worthy of clinical application. Trial registration Retrospectively Registered Trials ChiCTR2400087562 (07/30/2024)